"The lost decade": an MPT perspective. Issue 11 (9th November 2015) - Loviscek, Anthony
Abstract : Purpose: – The purpose of this paper is to test the efficacy of an application of modern portfolio theory (MPT) from 2000 through 2009, a period during which the annual rate of return on the S & P 500 is negative. The financial media have called this period "the lost decade" for investors. Design/methodology/approach: – Using monthly data, the author uses a series of annual out-of-sample tests to compare the risk-reward performances of MPT portfolios against those of the S & P 500. Findings: – The author finds that the MPT portfolios outperformed the S & P 500. During the "lost decade". They generated a cumulative return of over 77 percent compared to a cumulative return of −9.1 percent on the S & P 500. Moreover, the MPT portfolio β 's are low, ranging from 0.45 to 1.01, suggesting above-average risk-reward performances. Research limitations/implications: – The MPT portfolios are relatively small, and might not be well diversified. That said, they comprise a core set of securities that could help investors achieve a risk-reward performance that exceeds that of the S & P 500. Practical implications: – The results suggest that investors should not overlook the potential of MPT, despite its theoretical and practical limitations, to provide above-average returns at below-average risks. Originality/value: – This is the first study to show the efficacy of MPT during a period in which it was criticized at having failed investors when they needed it most.